Southwest Research-Extension Center, Field Day 1993 (Kansas Agricultural Experiment Station Research Reports, 1993)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 1993; SRP689; crops; tillage; irrigation; weed science; insect control